2019
DOI: 10.1007/s42452-019-1253-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the effect of obstacle upstream of a Savonius wind turbine

Abstract: The present studies investigate the performance of a small Savonius vertical axis wind turbine equipped with an upstream obstacle to guide the wind direction. The wind tunnel measurement was carried out in a test facility at the Mechanical Engineering Department, Institut Teknologi Sepuluh Nopember (ITS). The dynamic torque was measured using the brake dynamometer. Several variations of the obstacle orientations were investigated. Two different wind speeds of 2.48 m/s and 7.45 m/s were considered, that corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Putri et al experimental studied to assess the capability of an obstacle located upstream of a Savonius wind turbine to improve the power generated by the rotor. They stated that the obstacle and the Reynolds number have a small influence on the rotational speed of the loaded turbine (Putri et al, 2019). Akansu et al (2017) numerically investigated on a blade fixed pitch VAWT using NACA0021, NACA0015, NACA5520, and Clark-Y airfoils as a blade profile to assess its performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Putri et al experimental studied to assess the capability of an obstacle located upstream of a Savonius wind turbine to improve the power generated by the rotor. They stated that the obstacle and the Reynolds number have a small influence on the rotational speed of the loaded turbine (Putri et al, 2019). Akansu et al (2017) numerically investigated on a blade fixed pitch VAWT using NACA0021, NACA0015, NACA5520, and Clark-Y airfoils as a blade profile to assess its performance.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that Savonius wind turbines is applicable to helical Savonius wind turbines for small blockage ratios ranging from 3% to 8.3% (Jeon et al, 2015). Putri et al (2019) tested the performance of a small Savonius vertical axis wind turbine equipped with an upstream obstacle to guide the wind direction at 30000 and 90000 Reynolds number. They observed that that the mechanical torque and power generated by the rotor have been strongly affected by the obstacle and the Reynolds number has no significant impact on the rotor performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nabila et. al [4] using wind tunnel to investigate the effect of the upstream obstacle as wind deflector or guider on the Savonius wind turbine. By using the opening angle of obstacle have strongly to increase the rotor power and torque where the maximum performance at angle is 40 degrees.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the wind energy industry helps to decrease the dependency on fossil fuel. As a result, many researchers have studied different aspects of wind turbines numerically and experimentally [1][2][3]. Since wind energy sources, as well as suitable sites (both onshore and offshore locations) for installing wind turbines, are limited, wind turbines with higher efficiency are needed.…”
Section: Introductionmentioning
confidence: 99%